1997
DOI: 10.1111/j.1469-7793.1997.527bd.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin activates ATP‐sensitive potassium channels in the rat insulin‐secreting cell line, CRI‐G1

Abstract: Whole‐cell current‐clamp recordings demonstrate that leptin (0.3–10 nm) hyperpolarizes CRI‐G1 insulin‐secreting cells. This effect is slow on onset and is not reversed on washout of the leptin. Voltage‐clamp recordings indicate that leptin activates a potassium conductance in the presence of intracellular ATP (5 mm), but has no effect in its absence. Following activation of ATP‐sensitive K+ (KATP) current by diazoxide (0.2 mm), addition of leptin did not alter cell membrane potential or potassium current furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
88
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 26 publications
10
88
0
2
Order By: Relevance
“…As would be expected, leptin blocked insulin secretion by islets from ob/ob mice but not by db/db mice which lack the leptin receptor [65]. These effects may be mediated by the ATP-sensitive potassium channel [66,67].…”
Section: Regulation Of Leptin By Insulinmentioning
confidence: 58%
“…As would be expected, leptin blocked insulin secretion by islets from ob/ob mice but not by db/db mice which lack the leptin receptor [65]. These effects may be mediated by the ATP-sensitive potassium channel [66,67].…”
Section: Regulation Of Leptin By Insulinmentioning
confidence: 58%
“…Voltage clamp analysis (Fig. 4A) showed that leptin increased the mean cell slope conductance from 0.73 Ϯ 0.11 to 1.62 Ϯ 0.22 nanosiemens (n ϭ 19; p Ͻ 0.05), an action reduced by tolbutamide to 0.42 Ϯ 0.04 nanosiemens (n ϭ 14; p Ͻ 0.05), indicating that the increase in current responsible for the augmented slope conductance and ␤-cell hyperpolarization by leptin is due to K ATP channel opening (14,15,30). The presence of DMAT (10 M) in the electrode solution (and, therefore, cell interior) resulted in a mean resting membrane potential of Ϫ44.8 Ϯ 3.4 mV (p Ͼ 0.05 compared with control).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism seems to affect the phospholipase C (PLC)/protein kinase C (PKC)-mediated pathway regulating insulin secretion. Modulation by leptin of several steps in this pathway were described: lowering of intracellular Ca 2+ concentration and activation of ATP-sensitive K + channels (166,169,173); a speci®c inhibition of PLC-mediated insulin secretion, which is enhanced in ob/ob mice (167,174); and reduction of PKC, a Ca 2+ -dependent mediator in the second phase of the PLC signal pathway (167,170). The insulinsuppressive effect of leptin could also partly be mediated by activation of phosphodiesterase 3B (171,175), leading to suppression of cAMP levels and inhibition of GLP-1-stimulated insulin secretion.…”
Section: Effect Of Leptin On Insulin Secretionmentioning
confidence: 99%